2009
DOI: 10.1186/1471-244x-9-33
|View full text |Cite
|
Sign up to set email alerts
|

Mixed states vs. pure mania in the french sample of the EMBLEM study: results at baseline and 24 months – European mania in bipolar longitudinal evaluation of medication

Abstract: BackgroundTo describe the clinical course and treatment patterns over 24 months of patients experiencing an acute manic/mixed episode within the standard course of care.MethodsEMBLEM was a 2-year European prospective, observational study on outcomes of patients experiencing a manic/mixed episode. Adults with bipolar disorder were enrolled within the standard course of care as in/outpatients if they initiated or changed oral medication for treatment of acute mania. After completing 12 weeks of acute phase, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 23 publications
4
33
1
1
Order By: Relevance
“…Predictors of continuing antidepressants for up to 24 months of follow-up were mixed states, more previous depressive episodes, rapid cycling, and higher rates of depressive and anxiety symptoms at baseline (47, 48). …”
Section: Resultsmentioning
confidence: 99%
“…Predictors of continuing antidepressants for up to 24 months of follow-up were mixed states, more previous depressive episodes, rapid cycling, and higher rates of depressive and anxiety symptoms at baseline (47, 48). …”
Section: Resultsmentioning
confidence: 99%
“…In a sub-analysis of 771 patients in the two-year EMBLEM study, approximately one in three presented with a mixed episode, which was associated with a lower likelihood of recovery and greater use of antidepressant therapy compared to a pure manic state during follow-up (14). The Systematic Treatment Optimization Program for Early Mania (STOP-EM) project followed 53 patients presenting with a first episode of mania, and found that more than half experienced recurrence of a mood episode during the one-year follow-up, with a mean time to event of 7.9 months (15).…”
Section: Impactmentioning
confidence: 99%
“…There is growing evidence that early BPD mixed-states may be followed by particularly severe later morbidity that includes a great deal of dysphoria, depression and suicide-risk; moreover, their optimal treatment remains much less studied than mania or bipolar depression (Berk et al, 2005; Vieta et al, 2005; González-Pinto et al, 2007). There is some evidence that the nature of initial episodes, including mixed-states versus mania, can predict similar and greater morbidity during later follow-up (Azorin et al, 2009; Forty et al, 2009; Swan et al, 2009), usually based on retrospective or mid-course studies, rather than with systematic, prospective assessment of psychopathology in detail from onset (Baldessarini et al, 2010a). …”
mentioning
confidence: 99%